The impact of Primary SEAL small group interventions (silver set materials) on social and emotional outcomes for pupils - Otter, Clare (2010)
This study aimed to contribute to the small evidence-base on the Social and Emotional Aspects of Learning (SEAL) programme. SEAL is a school-based approach to developing children’s social and emotional skills. It was launched by the government in 2005 and has been adopted by schools across the UK. This study focused on the small group aspect of SEAL, which is aimed at children who are targeted for additional practice with their social and emotional skills. The researcher used a non-equivalent control group quasi-experimental design to evaluate the effectiveness of two of the small group SEAL interventions, New Beginnings and Getting On and Falling Out. Pupils, parents and teachers completed questionnaires before and after the interventions and, in the case of New Beginnings, around six weeks after the intervention ended. The level of fidelity to the government guidance was assessed through observations and interviews. No positive results were found for the New Beginnings intervention group in comparison with the control group, but there was some support for the Getting On and Falling Out intervention; with improvements in teacher-rated empathy, total emotional literacy and pro-social behaviour. In common with previous research, no effects were found for parent-ratings or for children who had been selected to take part in the interventions as role models. The results are discussed in terms of implications for practitioner educational psychologists and suggestions are made for further studies in this under-researched area.